A common factor in hypertrophic osteoarthropathy - Carroll, K. B. (1974)
Carroll, K. B. and Doyle, L. (1974).Thorax, 29, 262-264. A common factor in hypertrophic osteoarthropathy. Two cases of oesophageal disease with hypertrophic osteoarthropathy are presented. The unusual site of the primary lesion has prompted a review of the literature and led to the conclusion that there is a common innervation accounting for a common afferent arc which is an integral and basic part of the mechanism in this disorder.